2002
DOI: 10.1007/s00425-002-0844-z
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in ligand specificity of auxin-controlled elongation and auxin transport: comparing Zea and Vigna

Abstract: The plant hormone auxin affects cell elongation in both roots and shoots. In roots, the predominant action of auxin is to inhibit cell elongation while in shoots auxin, at normal physiological levels, stimulates elongation. The question of whether the primary receptor for auxin is the same in roots and shoots has not been resolved. In addition to its action on cell elongation in roots and shoots, auxin is transported in a polar fashion in both organs. Although auxin transport is well characterized in both root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 43 publications
6
22
0
Order By: Relevance
“…These inhibitory eVects were more pronounced in IAA-treated plants than on the HA-treated ones, suggesting that part of the HA eVects could activate other pathways beyond that of auxins. Although, IAA and HA induced only a non-statistically signiWcant increase (20-30%) of PR length, this tendency is in agreement with previous data, which showed that auxin concentrations as low as 10 ¡10 M could induce this trait in maize roots (Zhao et al 2002;Zandonadi et al 2007). On the other hand, the LR density was clearly enhanced in plants treated with IAA and HA, indicating that the average number of LR emergence events per area of the parent root increased.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These inhibitory eVects were more pronounced in IAA-treated plants than on the HA-treated ones, suggesting that part of the HA eVects could activate other pathways beyond that of auxins. Although, IAA and HA induced only a non-statistically signiWcant increase (20-30%) of PR length, this tendency is in agreement with previous data, which showed that auxin concentrations as low as 10 ¡10 M could induce this trait in maize roots (Zhao et al 2002;Zandonadi et al 2007). On the other hand, the LR density was clearly enhanced in plants treated with IAA and HA, indicating that the average number of LR emergence events per area of the parent root increased.…”
Section: Discussionsupporting
confidence: 90%
“…Further, the inhibitory eVect of vanadate on maize root elongation induced by 1 nM IAA was reported (Gouvêa et al 1997). Auxin can enhance PR elongation in maize seedlings at very low concentrations (Zhao et al 2002), possibly by H + -pump activation (Zandonadi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This means that the auxin receptor driving cell division shows a different ligand pattern than the receptor controlling cell elongation. If two receptors differ in their ligand pattern, they must be different receptors (Zhao et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the response of cell division to auxin has been shown recently to require the activity of a putative heterotrimeric G-protein, whereas the response of cell elongation was not dependent on this G-protein (Ullah et al, 2001(Ullah et al, , 2003. When different receptors are involved, they are expected to differ in their affinity for different ligands (Zhao et al, 2002). Different auxins should therefore affect cell division and cell elongation with different dose response relations.…”
mentioning
confidence: 99%
“…Hertel (1995) argued that ABP1 is not the auxin receptor for elongation growth. An alternative candidate discussed by Hertel et al was the plasma membrane-located auxin efflux carrier (Zhao et al, 2002). Recent studies indicated that soluble auxin receptors distinct from ABP1 participate in auxin-induced responses, at least at the plasma membrane (Kim et al, 1998(Kim et al, , 2000(Kim et al, , 2001 and for transcriptional regulation (Dharmasiri et al, 2003).…”
mentioning
confidence: 99%